Istikhdamu al-Intirnit Fi Ta'lim al-Lughah al-Arabiyyah Fi Indunisiya - Mohammad Zaelani Musonif (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
The aim of this research is to know the use of the Internet and its advantages and disadvantages in teaching Arabic. The method used is the qualitative. The results of the research were the use of the Internet in teaching the Arabic language through 1) search for materials and science sources, 2) a distance learning device, and 3) the assessment method in education. The benefits of the Internet in teaching Arabic appeared as follows: 1) the distribution of education to all students across country, 2) the learning process is not limited by time, 3) the possibility of choosing subjects or materials according to desires of teachers and students, 4) the duration of study was effective, 5) the materials are accurate and up-to-date. The disadvantages of the Internet in teaching Arabic are 1) the difficulty in controlling and monitoring students, 2) addiction addiction and 3) a high cost to access internet.